Determinação da sensibilidade elementar de amostras-padrão pelo método de flurescência de raios X por reflexão total - Silva, Káthia Takeda da [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
To determinate the multielemental concentrations in biological samples using the technique of total reflection X-ray fluorescence (TRFX) is essential the use of standard samples. The aim of this study is the determination of the sensitivities of the relevant elements in standard samples (Multi Element atomic spectroscopy standard solution in HNO3 I) prepared in three solutions with different and known concentrations. Based on the sensitivities of the elements contained in the multilelementar standard sample, it can estimate the sensitivity for an element found in the biological sample and consequently it is possible to determinate the concentration, even though the standard does not contain this element. The measurement of fluorescence was performed at the Brazilian Synchrotron Light Laboratory (LNLS) in Campinas

Para determinar as concentrações multielementares em amostras biológicas empregando a técnica de fluorescência de raios-x por reflexão total (TRFX) é imprescindível o emprego de padrões. O objetivo deste trabalho é a determinação das sensibilidades dos elementos de interesse num padrão (Multielement atomic spectroscopy standard solution I in HNO3) preparado em três soluções com concentrações diferentes e conhecidas. Com base nas sensibilidades dos elementos contidos na solução padrão multilelementar, pode-se estimar a sensibilidade para um elemento detectado na amostra e, conseqüentemente, estimar a sua concentração, mesmo que o padrão não contenha este elemento. A medida de fluorescência foi efetuada no Laboratório de Luz de Síncrotron (LNLS) de Campinas
Keywords: Fluorescencia de raio X